Innovative Waste Management Solutions: A Global Perspective Challenges and Opportunities and the Bangladesh Context - Ahmed, Rashed (AMPLITUDO : Journal of Science and Technology Innovation, 2025)
Waste management is a critical issue globally, and Bangladesh is no exception, facing significant challenges due to rapid urbanization, population growth, and inadequate infrastructure. This article explores comprehensive waste management strategies, including waste segregation, recycling, composting, and waste-to-energy technologies, emphasizing their environmental and health benefits. It examines the past and present waste management conditions in Bangladesh, highlighting the progress made and the persistent challenges. The article also compares waste management practices in neighboring countries like India, Bhutan, Sri Lanka, and Nepal, offering insights into potential improvements for Bangladesh. Emphasizing the need for public awareness, community involvement, and modern infrastructure, it calls for collaborative efforts to achieve sustainable waste management and environmental preservation in Bangladesh. This article examines the critical issue of waste management, emphasizing its importance in mitigating environmental pollution, conserving resources, and protecting public health. It provides a detailed analysis of various waste management strategies, including waste segregation, recycling, composting, and waste-to-energy technologies, highlighting their benefits and implementation challenges. Focusing on Bangladesh, the article traces the evolution of the country's waste management system, from past inadequacies to recent improvements, while acknowledging persistent issues such as rapid urbanization and insufficient infrastructure. Comparisons with waste management practices in neighboring countries like India, Bhutan, Sri Lanka, and Nepal offer valuable insights and potential strategies for Bangladesh to adopt. The article underscores the necessity of public awareness, community involvement, and robust infrastructure to achieve effective waste management. It calls for a collaborative approach involving government, private sector, NGOs, and local communities to develop sustainable solutions. By investing in modern waste management technologies and fostering responsible consumption and disposal habits, Bangladesh can address its waste management challenges, ensuring environmental preservation, public health, and overall national well-being.